Delayed gastric emptying and reduced postprandial small bowel water content of equicaloric whole meal bread versus rice meals in healthy subjects: novel MRI insights - Marciani, Luca; Pritchard, Susan E.; Hellier-Woods, C.; Costigan, C.; Hoad, Caroline; Gowland, Penny A.; Spiller, Robin C. (Nature Publishing Group, 2013)
BACKGROUND/OBJECTIVES: Postprandial bloating is a common symptom in patients with functional gastrointestinal (GI) diseases. Whole meal bread (WMB) often aggravates such symptoms though the mechanisms are unclear. We used magnetic resonance imaging (MRI) to monitor the intragastric fate of a WMB meal (11% bran) compared to a rice pudding (RP) meal. SUBJECTS/METHODS: 12 healthy volunteers completed this randomised crossover study. They fasted overnight and after an initial MRI scan consumed a glass of orange juice with a 2267 kJ WMB or an equicaloric RP meal. Subjects underwent serial MRI scans every 45 min up to 270 min to assess gastric volumes and small bowel water content and completed a GI symptom questionnaire. RESULTS: The MRI intragastric appearance of the two meals was markedly different. The WMB meal formed a homogeneous dark bolus with brighter liquid signal surrounding it. The RP meal separated into an upper, liquid layer and a lower particulate layer allowing more rapid emptying of the liquid compared to solid phase (sieving). The WMB meal had longer gastric half emptying times (132±8 min) compared to the RP meal (104±7 min), P<0.008. The WMB meal was associated with markedly reduced MRI-visible small bowel free mobile water content compared to the RP meal, P<0.0001. CONCLUSIONS: WMB bread forms a homogeneous bolus in the stomach which inhibits gastric sieving and hence empties slower than the equicaloric rice meal. These properties may explain why wheat causes postprandial bloating and could be exploited to design foods which prolong satiation.